A comparative study of metalloestrogens in blood and ectopic endometrial tissue in women with endometriosis and matched controls - Silva, N.; Senanayake, H.; Peiris-John, R.; Wickremasinghe, R.; Sathiakumar, N.; Waduge, V. (University of Colombo, 2011)
Environmental pollution has been cited as a potential cause for an increase in the prevalence of endometriosis. Heavy metals are known to have oestrogenic properties. Several studies have reported high serum concentrations of heavy metals in patients with endometriosis. A study has demonstrated increased amount of iron in ectopic endometrial tissue. The presence of other metals in ectopic endometrial tissue, either qualitatively or quantitatively is yet to be described in literature